A numerical solution for Duffing-Van Der Pol oscillators using a backward difference formulation - Rasedee, AFN; Sathar, MHA; Ijam, HM; Othman, KI; Ishak, N; Hamzah, SR (Amer Inst Physics, 2024)
The study of chaotic motion in periodic self-excited oscillators are an area of interest in science and engineering. In the current research, a numerical solution hi backward difference form is proposed for solving these chaotic motions in periodic-self excited oscillators. Study conducted in this article focuses on chaotic motions in the form of Duffing-Van Der Pol Oscillators. A backward difference formulation in predictor-corrector (PeCe) mode is introduced for solving these Duffing-Van Der Pol directly. Numerical simulations provided will show the accuracy of the PeCe backward difference formulation.